Still worlds apart: flourishing in people with mental health problems. Issue 3 (3rd July 2020) - Allen, Rosie Elizabeth; Carson, Jerome; Merrifield, Bethany; Bush, Stacey
Abstract : Purpose: The purpose of this paper is to compare a group of service users with mental health problems with a community comparison group of gym attenders. Design/methodology/approach: Cross-sectional questionnaire surveys were conducted at a large gym (n = 181) and two community mental health facilities (n = 127) in the Greater Manchester area using a convenience sample approach. All participants completed the PERMA Scale, a measure of flourishing. Findings: Gym attenders scored significantly higher on the five elements of PERMA. Their physical health ratings were almost double. They also had significantly lower levels of negative emotions and loneliness and higher levels of overall happiness. Research limitations/implications: This study only considered levels of flourishing. Previous studies of quality of life have shown similar disparities between people with mental health problems and others. Practical implications: Professor Seligman has claimed that improving levels of flourishing is the main aim of positive psychology. The present study suggests this may be especially challenging for people with mental health problems. Social implications: The concept of flourishing could provide a more positive non-medical focus for mental health services, in the development of what some have called positive psychiatry. This complements the current recovery model. Originality/value: To the best of the authors' knowledge, this is one of the first studies to compare flourishing levels between individuals with mental health problems and a community comparison group using the PERMA Scale.